Evolution of sensory analysis attributes and volatile aging markers in bottle fermented craft beers during storage at different temperatures. (October 2022) - Valentoni, Antonio; Santoru, Antonio; Sanna, Manuela; Fanari, Mauro; Porcu, Maria Cristina; Fadda, Angela; Sanna, Daniele; Pretti, Luca
Highlights: High temperature drastically reduces the shelf life in bottle conditioning beers. No differences were observed in standard quality parameters and volatile profiles in beer stored at 6 °C and 22 °C in our experimental observation time. No differences were observed between the use of traditional caps or oxygen scavenging bottle caps in our experimental conditions. β-Damascenone and furfuryl ethyl ether play an important role on sweet and paint aged beer aroma notes observed in sample stored at 45 °C. Abstract: Beer oxidation is strictly linked to its shelf life. Chemical variation in aldehydes, higher alcohols, hops bitter substances and esters, also could have a role key in stale flavor. Bottle refermentation,  is the method by which beer in the bottle is made sparkling and is often used in craft brewing. Before the process an amount of oxygen in the headspace can be a potential source of oxidation. We investigated the effect of oxygen and temperature during storage of refermented craft beer in bottles with standard and oxygen scavenger caps. Beer was stored for 13 weeks at 6, 22 and 45 °C for forced aging, and monitored by technological analysis,  SPME (-) and - MS (-), Electron Paramagnetic Resonance (EPR). At 45 °C, the samples showed a decrease of International Bitterness Units and an increase in color and concentrations of oxidized molecules, and other related with the high temperature (aldehydes and furanic compounds respectively). No differences were observed between samples stored at 6 and 22 °C. Sensory analysis showed differences in the perception of paint, sweet, cardboard and freshness attributes in the samples stored at 45 °C. No differences were observed in the use of standard and oxygen scavenger caps.